The Korean nights entertainments (comic stories) - Ha, Tae Hung (Yonsei University Press : Seoul, 1970)
Contains 112 plays representing Korean humor of olden times.
1
Keywords: Korean wit and humor -- Translations into English; English wit and humor -- Translations from Korean